Curbing shocks to corporate liquidity: The role of trade credit - Niklas Amberg; Tor Jacobson; Erik von Schedvin; Robert M. Townsend (Sveriges Riksbank, 2016)
Using data on exogenous liquidity losses generated by the fraud and failure of a cash-intransit firm, we demonstrate a causal impact on firms' trade credit usage. We find that firms manage liquidity shortfalls by increasing the amount of drawn credit from suppliers and decreasing the amount issued to customers. The compounded trade credit adjustments are at least as great, if not greater than corresponding adjustments in cash holdings, suggesting that trade credit positions are economically important sources of reserve liquidity. The underlying mechanism in trade credit adjustments is in part due to shifts in credit durations - both upstream and downstream.
Keywords: D22; G30; 330; Liquidity management; Trade credit; Risk sharing